Application of gender and optimizing the function of the board of commissioners in supervising the practice of corporate earnings management - Gandy Wahyu Maulana Zulma; Misni Erwati; Fitri Chairunnisa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The urgency of this research is importantto empirically examine the impact of the characteristics of the board of commissioners on earnings management practices in Indonesia by considering gender diversification factors in optimizing the supervisory function of the company's board of commissioners. The sampling method used is purposive sampling with specific criteria on companies listed on the IDX with a research period of 2018-2019 with a total sample of 368 firm years of observation. The results showed that the independence of the board of commissioners was not proven to affect accrual earnings management. However, it was proven to have a negative effect on real earnings management practices. In addition, the size of the board of commissioners is proven to have a positive effect on accrual earnings management and company real earnings management. The role of gender diversification in reducing earnings management practices is proven. Three or more female commissioners can reduce accrual earnings management practices and increase real earnings management practices in companies. In addition, the role of gender diversification is not proven to strengthen the negative effect of the independence of the board of commissioners on earnings management. However, the role of gender diversification where there are three or more people in the size of the company's board of commissioners can further reduce accrual earnings management and real earnings management.